2022
DOI: 10.2106/jbjs.oa.21.00123
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Different Plate Configurations for Midshaft Clavicle Fracture Fixation

Abstract: Background: Dual-plate constructs have become an increasingly common fixation technique for midshaft clavicle fractures and typically involve the use of mini-fragment plates. The goal of this technique is to reduce plate prominence and implant irritation. However, limited biomechanical data exist for these lower-profile constructs. The study aim was to compare dual mini-fragment orthogonal plating with small-fragment clavicle plates for biomechanical noninferiority and to determine if an optimal plate configur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In contrast to past studies, recent investigations showed surgical fixation leads to lower rate of non-union and better functional outcomes in patients with displaced midshaft clavicular fractures. [ 7 ] However, thin soft tissue coverage of this area makes it susceptible to surgical-related wound complications and device prominence. Single superior plating of the clavicle bone is an accepted method of surgical fixation for displaced midshaft clavicular fractures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to past studies, recent investigations showed surgical fixation leads to lower rate of non-union and better functional outcomes in patients with displaced midshaft clavicular fractures. [ 7 ] However, thin soft tissue coverage of this area makes it susceptible to surgical-related wound complications and device prominence. Single superior plating of the clavicle bone is an accepted method of surgical fixation for displaced midshaft clavicular fractures.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Newly, some biomechanical studies showed the advantages of midshaft clavicular fracture fixation with double mini-plates. [ 7 ] Ziegler et al . reported similar biomechanical outcomes of double-plating construct in comparison with superior or anteroinferior single plating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors had previously studied clavicle fixation with FE analysis and found that when screw holes were positioned close to the fracture site, there was a significant increase in stress on the plate and clavicle [64,65]. This indicates that screw positioning close to the fracture can have a significant effect on the stress pattern in the plate fixation system [66]. These changes in stress patterns can potentially affect the healing process, long-term fracture stability, rehabilitation program, and clinical outcomes [67].…”
Section: Discussionmentioning
confidence: 99%
“…However, dual plate constructs had similar torsional and bending stiffness to anterior single plate constructs. 46 Though we can extrapolate some data from adult populations, none of these studies were specifically performed in the adolescent or pediatric population and differences between plating position in this population remain an open question. Despite increased biomechanical stability, there are no studies in a pediatric population to suggest that dual plate constructs improve clinical outcomes.…”
Section: Managementmentioning
confidence: 99%